Inflammatory Myofibroblastic Tumor: Rare Manifestation in Face - Silva, William Phillip Pereira da; Zavarez, Larissa Balbo; Zanferrari, Fernando Luiz; Schussel, Juliana Lucena; Faverani, Leonardo Pérez; Jung, Juliana Elizabeth; Sassi, Laurindo Moacir (Wolters Kluwer, 2017)
Inflammatory myofibroblastic tumor, also known as inflammatory pseudotumor and plasma cell granuloma, is a tumor that occurs most often in the lungs, abdomen, skin, soft tissue, genital system, and mediastinal. Before surgery, the diagnosis is difficult to establish because of its diverse manifestations. In the head and neck, manifestation is rare and may occur in the upper respiratory tract, soft tissues, orbits, and skull base. This article aims to report a rare manifestation of the disease in the face, highlighting the importance of a correct diagnosis to determine the most appropriate form of treatment, in male patient, leucoderma, 22 years old, with complain of a painless unilateral growth in the left cheek, beginning 2 months before and with progressive growth.